Studi Literatur: Pengaruh Problem Based Learning Terhadap Keterampilan Berpikir Kritis Siswa Pada Pembelajaran Biologi - dinda sawitri; Syamsurizal (Al-Alam: Islamic Science Education Journal, 2025)
This study aims to analyze and synthesize the impact of the Problem-Based Learning (PBL) model on critical thinking skills in biology education through a literature review. The research method used was a Systematic Literature Review (SLR) by analyzing six accredited scientific articles from the Google Scholar database spanning the years 2020–2025. The results indicate that the consistent application of the PBL model has a significant positive impact on improving students’ critical thinking skills compared to conventional models. This is evidenced by the higher average posttest scores of the experimental class and the results of statistical tests with a significance value of 0.000. This improvement is attributed to the PBL model presenting authentic problems that encourage students to conduct independent investigations, in-depth analysis, and group collaboration in finding solutions. The conclusion of this study is that the PBL model is an effective strategy for equipping students with critical and analytical thinking skills in biology.